ANALISIS PENERAPAN SAK EMKM DALAM MENYUSUN LAPORAN KEUANGAN UMKM - Purba, Mortigor Afrizal; Natalia, Erni Yanti (JURSIMA, 2023)
Seeing the importance of applying accounting for UMKM, the IAI as a professional organization as well as a compiler of Financial Accounting Standards (SAK) through the Financial Accounting Standards Board (DSAK) composes accounting standards that are consistent with the characteristics of UMKM. Based on the results of the study, it can be concluded that, (1) Bookkeeping carried out on UMKM is still limited to business reports which are prepared not in accordance with financial accounting standards, but the entity considers them as financial statements. (2) The entity has not conducted accounting procedures in accounting. (3) UMKM have not implemented SAK-EMKM. (4) The entity has not been able to present financial statements in accordance with the SAK-EMKM.